Optimizing the Fortification of Flour of Palmyra New Shoots Tubers with Powders Deriving from Cowpea Beans and Moringa Leaflets for Porridge Making - , Mahan Makado Romuald; , Konan N’Guessan Ysidor; , Koffi N’dri Emmanuel; , Deigna-Mokey Viviane; , Coulibaly Adama; , Sidibé Daouda; , Biego Godi Henri Marius (Archives of Current Research International, 2016)
This study aims to apply central composite design for the fortification of the meal deriving from new shoots tubers of Palmyra (Borassus aethiopum M.) with powders of Cowpea (Vigna unguiculata W.) beans and Moringa (Moringa oleifera L.) leaflets for gathering simultaneous maximization of the intensity of agreability, index of bitterness (low bitterness) and fluidity of the porridge resulting from the composite flour. Thus, the samples were collected between August and December 2015 from three localities, especially in the areas of Dimbokro, Toumodi and Didiévi, in the center of Côte d’Ivoire. Once acquired, the samples were sorted, washed, dried and processed into flour. Then, a central composite design was applied to determine the adequate proportions of each component of the composite flour in order to derive in a higher sensorial quality porridge. The independent variables selected for the study design were quantities of Palmyra flour (X1), Cowpea beans powder (X2) and Moringa leaflets powder (X3). The results highlighted needs of 50% of Palmyra, 30% of Cowpea and 20% of Moringa in the deriving composite flour for succeeding in acceptable porridge fitting with overall sensorial parameters. Accounting these conditions, the resulted porridge recorded an agreability intensity of 6.93±0.3/9, a bitterness index of 0.57±0.04/1 and a fluidity level of 6.67±0.2/9. The characteristics of this porridge are close to those predicted by the central composite design with values of 7.12, 0.55 and 6.82 for respective agreability intensity, bitterness index and fluidity.